International Socialization in Europe European Organizations, Political Conditionality and Democratic Change - Schimmelfennig, F.; Engert, S.; Knobel, H.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
At the end of the Cold War, the Western international community embarked on a large-scale project of promoting democratic change and consolidation in Eastern Europe. This book explains its mixed results. It examines the strategies of European organizations and the conditions of their success and failure.
Keywords: European Union; Comparative politics; Political science; Democracy; International relations; European Union Politics; Comparative Politics; Political Science; Democracy; International Relations